Measuring Oil-Price Shocks Using Market-Based Information - Wu, Tao (IMF Working Papers; Working Paper, 2012)
We study the effects of oil-price shocks on the U.S. economy combining narrative and quantitative approaches. After examining daily oil-related events since 1984, we classify them into various event types. We then develop measures of exogenous shocks that avoid endogeneity and predictability concerns. Estimation results indicate that oil-price shocks have had substantial and statistically significant effects during the last 25 years. In contrast, traditional VAR approaches imply much weaker and insignificant effects for the same period. This discrepancy stems from the inability of VARs to separate exogenous oil-supply shocks from endogenous oil-price fluctuations driven by changes in oil demand.